ANALISIS PERBANDINGAN DAYA HAMBAT EKSTRAK PIROLISIS DAN EKSTRAK MASERASI Nicotiana tabacum VAR. VIRGINIA TERHADAP Aspergillus niger SECARA IN VITRO - Kholda Taqiyyun, (2021)
Aspergillus niger is one of the most common fungi that can cause otomycosis. The high recurrence rate of this disease can increase the risk of resistance to antifungal agents, so it is necessary to search for antifungal alternatives derived from herbs. Tobacco leaves are known to contain alkaloids, flavonoids, and terpenoids, which can inhibit fungal growth. The purpose of this study was to compare the inhibition of pyrolysis extract and maceration extract of tobacco leaves (Nicotiana tabacum) as antifungals against the growth of A. niger in vitro. This study used an experimental method with samples of pyrolysis extraction and maceration extraction of tobacco leaves at concentrations of 20%; 40%; 60%; 80%; and 100%. The antifungal test method used is the well diffusion method by observing the fungal growth inhibition zone around the well. One-way ANOVA test analysis with p-value <0.05 showed that there were significant differences in each extraction in inhibiting A. niger. The average results of the largest inhibition zones formed in the pyrolysis and maceration extracts were 36.72 mm and 16.05 mm, respectively. Based on the results of this study, it was shown that the content of alkaloids, flavonoids, and terpenoids found in the pyrolysis and maceration extracts of tobacco leaves had antifungal properties in inhibiting the growth of A. niger.